Analysis of fatalities involving amphetamine in Jazan, Saudi Arabia - Ibraheem M., Attafi (2021)
Amphetamine use is associated with high tendence of homicidal or suicidal deaths and fatalities making amphetamine a persistent area of concern. This study analyzed fatalities associated with amphetamine use in Jazan city, Saudi Aarabia from 2018 to 2020 and investigated the postmortem tissue distribution of amphetamine. The fatalities associated with the use of amphetamine and other drugs were increased from 18% in 2018to 52% in 2019 and to 80% in 2020 compared to all fatalities associated with amphetamine alone. Suicidal people had the highest average amphetamine blood concentrations with a 90th percentile concentration of 7.6 mg/L. In those who use amphetamine in combination with other drugs, suicidal and homicidal deaths are more common than those who use amphetamine alone. The results demonstrate the need to raise the awareness of the increasing number of deaths associated with amphetamine use in combination with other drugs in health care providers.